Being a right parent: a narrative review of the theory and practice of parental involvement in sport parenting - Liu, Chuchen; Zhao, Fang; Nong, Shujun; Lin, Zhiyi (Frontiers in Psychology, 2024)
The family is the first classroom for children and adolescents to learn and grow, and parents' behavior plays an important role in influencing their children's development, which is also evident in the process of sport participation. The main purpose of this study is to summaries the specific theoretical and practical experiences of parents in sport parenting based on a comprehensive review of the types and functions that constitute parental involvement in sport parenting and the process of their practice. To this end, this study used narrative research as the main research method and searched the literature related to parents' involvement in parenting through sport using the Web of Science database. Using the theoretical underpinnings of parents' implementation of sport parenting and their role practice, studies were screened and 39 pieces of literature were finally obtained. The study found that in terms of theoretical underpinnings, the existing types of parental involvement in sport parenting can be broadly categorized into four types: authoritative, authoritarian, permissive and rejecting-neglecting. The functions of parental involvement in sport education have two dimensions: promoting sport development and promoting socialization. Based on a review of their theories, we further summaries and conclude the consequences of action and appropriate practices of parental practices in three scenarios: on the sports field, on the way home and in the private space. It is assumed that parents, when participating in sports parenting, need to: (Ⅰ) regulate their own behavior in order to avoid psychological pressure on their children due to inappropriate behavior; (Ⅱ) play different roles at different stages of their children's sports development; (Ⅲ) should not put too much pressure on their children's performance. Based on these reviews of the theory and practice of parental involvement in sport parenting, this study further examines the theoretical limitations of the established research. It is argued that future research should pay attention to the differences between the identities and expectations of parents or children of different genders about their sport parenting, in addition to the differences in parental involvement in sport parenting and different practices in different cultural contexts.